Five-year strategic plan for Panabo Multi-Purpose Cooperative (PMPC) - Padua, Christine H. (School of Management, University of the Philippines Mindanao, 2010)
This paper aimed to develop a five-year strategic plan for Panabo Multi-Purpose Cooperative from 2011-2014. PMPC is a credit facility which started its operation in 1965 in Panabo City. The study adopted the conceptual framework of Fred David which includes Strategy Formulation, Strategy Implementation and Strategy Evaluation. Data and information needed in the study was obtained through interview, cooperative?s annual reports, books, reading materials and the internet. The study only focuses on PMPC?s operation in Region XI. For the past 5 years PMPC?s operation have grown as reflected in its increasing net surplus, revenues, assets and equities. By 2008, its assets stood at 288 million and a net surplus of 17 million. However based on the financial ratios, its Return on Sales (ROS) and Return on Equity (ROE) is decreasing while Asset Turn-Over shows only a slight improvement. The external environment of the cooperative was assessed on the macro-environment and micro-environment level. This determines the opportunities and threats facing the cooperative. The micro-environment includes political-legal, economic, socio-cultural, environmental and technological environment. Porters Five Forces Analysis was used to analyze the micro environment of the cooperative. These forces focus on the industry and competitive environment of the cooperative. An External Factor Evaluation (EFE) shows how the cooperative responds to the identified opportunities and strengths. PMPC yields an EFE score of 2.66 which concludes that PMPC?s ability to react to its external environment is deemed satisfactory. An EFE score of <2.5 indicates that the organization may lack the capacity to capitalize opportunities and counter threats. The internal environment analysis focuses on the assessment of the cooperatives strengths and weaknesses considering the different functional areas to wit: general management, finance, human resource, operations, and marketing and information systems. The Internal Factor Evaluation (IFE) shows a score of 2.67 concludes that PMPC is marginally strong. A score of <2.5 indicates a weak internal position. Taking into account the external and internal environment of the cooperative, a goal was put in place: to have an annual increase of 21% in its total assets to achieve 700 million assets by 2014 and an annual membership growth of 22% to achieve 30,000 members by 2014. SWOT (Strength, Weaknesses, Opportunities, and Weaknesses) Matrix was used in generating strategic options to achieve the long term goals of the cooperative. The cooperative?s strengths were matched with the opportunities and threats and likewise its weaknesses matched with opportunities and threats. The strategies generated were mutually grouped into 2: Market Penetration and Market Development. The best strategic option was determined using the Quantitative Strategic Planning Matrix (QSPM). Based on the Matrix, Market Penetration got a score of 5.11 while Market Development got 4.95 Higher score indicates more attractive strategy considering all external and internal factors that could affect the strategic decision. Implementing activities in each functional area (organization and Human Resource, Marketing, Finance and Operations) were formulated to support the chosen strategy. If implemented, the cooperative can increase it total assets to 1.05 billion by 2014 and attain 30,000 members by 2014. Control systems were also set to monitor and evaluate the implemented strategies. Strategy evaluation activities include reviewing the strategy yearly or as deemed necessary, organizational performance assessment and taking corrective actions if deviations occur against set targets. Contingency plan was set in case plans do not occur as expected.